A New Perspective on the Treatment of Alzheimer's Disease and Sleep Deprivation-Related Consequences: Can Curcumin Help? - Kuepeli Akkol, Esra; Bardakci, Hilal; Yuecel, Cigdem; Seker Karatoprak, Goekce; Karpuz, Buesra; Khan, Haroon (HINDAWI LTD, 2022)
Sleep disturbances, as well as sleep-wake rhythm disorders, are characteristic symptoms of Alzheimer's disease (AD) that may head the other clinical signs of this neurodegenerative disease. Age-related structural and physiological changes in the brain lead to changes in sleep patterns. Conditions such as AD affect the cerebral cortex, basal forebrain, locus coeruleus, and the hypothalamus, thus changing the sleep-wake cycle. Sleep disorders likewise adversely affect the course of the disease. Since the sleep quality is important for the proper functioning of the memory, impaired sleep is associated with problems in the related areas of the brain that play a key role in learning and memory functions. In addition to synthetic drugs, utilization of medicinal plants has become popular in the treatment of neurological diseases. Curcuminoids, which are in a diarylheptanoid structure, are the main components of turmeric. Amongst them, curcumin has multiple applications in treatment regimens of various diseases such as cardiovascular diseases, obesity, cancer, inflammatory diseases, and aging. Besides, curcumin has been reported to be effective in different types of neurodegenerative diseases. Scientific studies exclusively showed that curcumin leads significant improvements in the pathological process of AD. Yet, its low solubility hence low bioavailability is the main therapeutic limitation of curcumin. Although previous studies have focused different types of advanced nanoformulations of curcumin, new approaches are needed to solve the solubility problem. This review summarizes the available scientific data, as reported by the most recent studies describing the utilization of curcumin in the treatment of AD and sleep deprivation-related consequences.